2016
DOI: 10.2337/db16-0381
|View full text |Cite|
|
Sign up to set email alerts
|

Adipocyte Glucocorticoid Receptor Deficiency Attenuates Aging- and HFD-Induced Obesity and Impairs the Feeding-Fasting Transition

Abstract: Glucocorticoids (GCs) are important regulators of systemic energy metabolism, and aberrant GC action is linked to metabolic dysfunctions. Yet, the extent to which normal and pathophysiological energy metabolism depend on the GC receptor (GR) in adipocytes remains unclear. Here, we demonstrate that adipocyte GR deficiency in mice significantly impacts systemic metabolism in different energetic states. Plasma metabolomics and biochemical analyses revealed a marked global effect of GR deficiency on systemic metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 55 publications
0
81
3
Order By: Relevance
“…It is noteworthy that some of the actions of GCs may result from cross talk between tissues. For example, GCs promote lipid catabolism in adipose tissue, yet whether they drive lipolysis by directly or solely acting on adipocytes remains unclear [68]. It should also be mentioned that GCs exert rapid effects occurring in minutes that are insensitive to inhibitors of DNA transcription and protein synthesis [9].…”
Section: Gr: a Nuclear Receptor With Widespread Physiological Impactmentioning
confidence: 99%
“…It is noteworthy that some of the actions of GCs may result from cross talk between tissues. For example, GCs promote lipid catabolism in adipose tissue, yet whether they drive lipolysis by directly or solely acting on adipocytes remains unclear [68]. It should also be mentioned that GCs exert rapid effects occurring in minutes that are insensitive to inhibitors of DNA transcription and protein synthesis [9].…”
Section: Gr: a Nuclear Receptor With Widespread Physiological Impactmentioning
confidence: 99%
“…In adipose tissue, GR is thought to mediate the lipolytic effects of GC treatment and has been found to be crucial for lipid mobilization in the postabsorptive state as well as in chronic GC exposure [4][5][6]. White adipose tissue (WAT) mainly acts as an energy storage organ, coping with excessive energy intake by storage in the form of triacylglycerol, and in turn liberating non-esterified fatty acids in periods of nutrient demand by other tissues or following lipolytic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue, GR is thought to mediate the lipolytic effects of GC treatment and has been found to be crucial for lipid mobilization in the postabsorptive state as well as in chronic GC exposure [4][5][6]. Recent studies, however, have contested this notion: GR-deficient murine preadipocytes were shown to suffer only from a delay in triglyceride (TG) accumulation, and adiponectin-Cre-mediated deletion of GR led to no morphological difference in WAT depots [4,9]. GCs are contained in most in vitro adipogenic differentiation cocktails, and GR was found to bind cooperatively with CEBPB at transcriptional hotspots in early adipogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations